Isothermal and nonisothermal crystallization kinetics of fully bio‐based polyamides. Issue 7 (15th April 2016) - He, Miaomiao; Wei, Tao; Zhang, Liqun; Jia, Qingxiu
Abstract : We studied the crystallization behaviors of bio‐based BDIS polyamides synthesized from the following biomass monomers: 1, 4‐butanediamine (BD), 1, 10‐decanediamine (DD), itaconic acid (IA), and sebacic acid (SA). Isothermal crystallization, melting behavior, and nonisothermal crystallization of BDIS polyamides were investigated by differential scanning calorimetry (DSC). The Avrami equation was used to describe the isothermal crystallization of BDIS polyamides. The modified Avrami equation, the Ozawa equation, the modified Ozawa equation, and an equation combining the Avrami and Ozawa equations were used to describe the nonisothermal crystallization. The equilibrium melting point temperature of BDIS polyamide was determined to be 163.0°C. The Avrami exponent n was found to be in the range of 2.21–2.79 for isothermal crystallization and 4.10–5.52 for nonisothermal crystallization. POLYM. ENG. SCI., 56:829–836, 2016. © 2016 Society of Plastics Engineers